2017
DOI: 10.1039/c7nr04056c
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric in vivo auditioning of targeted silver nanoparticles

Abstract: Attaching affinity ligands to nanoparticles (NPs) increases selectivity for targeting cells and tissues, and can result in improved sensitivity and reduced off-target toxicity in diagnostic and therapeutic systems. The decision over key features – NP size, shape, coating strategies and targeting ligands for clinical translation is often hampered by a lack of quantitative in vivo NP homing assays. Sensitive, internally controlled assays are needed which allow for quantitative comparisons (auditions) among vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…For passively targeted preparations, the size of the particle s directly affects the distribution of the drug in vivo. Nanoparticles with different sizes have different in vivo distribution characteristics (24). From the perspective of medication safety, the smallest capillary diameter of the human body is about 4 µm, so the size of the intravenously injected nanoparticles should be less than this limit.…”
Section: Discussionmentioning
confidence: 99%
“…For passively targeted preparations, the size of the particle s directly affects the distribution of the drug in vivo. Nanoparticles with different sizes have different in vivo distribution characteristics (24). From the perspective of medication safety, the smallest capillary diameter of the human body is about 4 µm, so the size of the intravenously injected nanoparticles should be less than this limit.…”
Section: Discussionmentioning
confidence: 99%
“…To validate our approach to in vivo homing peptide identification, we decided to perform a model screen focused on the enrichment and tissue distribution analyses of a known brainselective peptide, CAGALCY (20,21), spiked into a low complexity peptide phage library. We showed that by using the differential binding approach we can not only select for CAGALCY as a brain homing peptide, which would be possible by conventional enrichment analysis, but also profile its biodistribution and selectivity across organs.…”
Section: In Vivo Homing Of Individual Peptide Phagesmentioning
confidence: 99%
“…Moreover, healthy organs can be specifically targeted with homing peptides. Examples are brain homing peptide CAGALCY (20,21) and prototypic C-end Rule (CendR) peptide RPARPAR that upon intravenous administration accumulates in lungs and heart (7).…”
Section: Introductionmentioning
confidence: 99%
“…Structure-activity relationship analysis of CAGALCY peptide demonstrated the free carboxylic acid side chain and N-tyrosine as the key pharmacophore of the peptide (Fan et al 2007). CAGALCY coupled to silver NPs improved their brain homing effect in vivo (Toome et al 2017). Finally, Urich et al identified RLSSVDSDLSGC by next-generation sequencing (NGS) of T7 display phage library screened against in-vivo BBB model (rat).…”
Section: Peptides As Carriers To Deliver Therapeutics Into the Brainmentioning
confidence: 99%